STATISTICAL ANALYSIS OF THE COMPOSITION OF FOREIGN INVESTMENTS (World Economics and Finance Bulletin, 2024)
Today, several reforms are being carried out in our country to improve the regional investment potential. Investment, which is one of the main levers of today's economy, and increasing its attractiveness is one of the priority tasks facing every country.
Keywords: Investment; statistical research; economic development